A simple and reliable, optical all-fibre, data acquisition trigger signal for fibre-laser asynchronous optical sampling systems. (18th March 2019) - Yang, Xue; Su, Bo; Wu, Yaxiong; Zhang, Hongfei; He, Jingsuo; Jones, David R
Abstract: We present an optical all-fibre data acquisition trigger signal particularly suited for fibre-laser asynchronous optical sampling systems. We demonstrate that in the case where the laser spectra are inadequately matched and deliver a weak interferometric signal, post electronic filtering can significantly enhance the signal, removing the necessity for optical band-pass filtering. The method requires no free-space optics and no precise alignment of focused beam spots, eliminating beam pointing stability and walk-off issues.